IDENTIFICATION OF THE ANCIENT LAKES BASED ON GRAVITY METHODS IN BOROBUDUR TEMPLE - Nanda Ridki Permana; Fadhlur Rahman; Fardhan Rafshan Zani; Dias Shafa; Dhika Faiz Fadrian (Engineering Faculty Universitas Lampung, 2023)
Indonesia is a country that's well known for its heritages. One of the heritages is Borobudur Temple. Several studies say that the Borobudur was enclosed by a lake. Therefore, this study aims to see the remains of an ancient lake below the surface with gravity method. The process stage begins with obtaining the CBA (Complete Bouger Anomaly) and continues by separating the anomaly with a Bandpass Filter, and followed with 3D inverse modeling and FHD (First Horizontal Derivative) analysis. According to the residual map, there are only minor anomalies in the west, south, and east, ranging in magnitude from -0.539 to (-0.209) mGal. This anomaly is consistent with the location of the ancient lake around Borobudur. In the meantime, the 3D modeling of the FHD study reveals a geologic structure surrounding the Borobudur with an anomaly ranging from 0.00289 to 0.00480 mGal. A deposit layer thought to be an ancient lake is visible between 50 and 525 meters in depth over the east and west sides of the Borobudur temple, and beneath it is visible between 250 and 525 meters. This depth map provides additional evidence that the ancient lake beneath the Borobudur is located between 250 and 525 meters.